TEKNIK PENGOLAHAN IKAN LAUT - P, Sutriyati; Badraningsih, Badraningsih; E, Prihastuti (Universitas Negeri Yogyakarta, 2004)
The training of the fish processing is meant to socialize knowledge and skills in fish processing safety and healthy to be consumed for the fish sellers in Trisik Beach, Kulon Progo, Yogyakarta.The 15 fish sellers attended the training from Trisik Village. The training was conducted 5 times consisting of one session of theory and 4 sessions of a practices. The methods of the training were lecturing, demonstrating and practicing on the spot. The evaluation was done after the training had finished.The result of the training showed that the participants mastered thetraining material given covering: 1) hygiene in fish processing, 2) fish processing for preserving products i.e fish crackered and smoked, and 3) fish processing for ready-served food such as siomay, ikan acar kuning and saos asam manis that are served hygienically. The result of the training has been applied in warung PKK Trisik Village, Kulon Progo, Yogyakarta.Key word: training.fish processing